2003
DOI: 10.1038/sj.onc.1206071
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between BRCA2 and replication protein A is compromised by a cancer-predisposing mutation in BRCA2

Abstract: Mutations in the BRCA1 and BRCA2 genes predispose women to familial, early-onset breast cancer. Both the BRCA1 and BRCA2 proteins appear to function in the homologous recombination pathway of DNA doublestrand break repair. Both BRCA1 and BRCA2 have also been implicated in transcription by RNA polymerase II, for both proteins have domains which, when tethered adjacent to a promoter, can activate transcription. In experiments reported here, we have used protein affinity chromatography and coimmunoprecipitation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
66
2
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 37 publications
(49 reference statements)
1
66
2
1
Order By: Relevance
“…Only BRCA2 Y42C was thought to be a pathogenic mutation. Y42 is a highly conserved amino acid and Y to C is a radical amino-acid change, compromising in vivo the interaction between BRCA2 and replication protein A (Wong et al, 2003). All splice site mutations were studied at the RNA level Claes et al, 2003).…”
Section: Brca1 and Brca2 Mutationsmentioning
confidence: 99%
“…Only BRCA2 Y42C was thought to be a pathogenic mutation. Y42 is a highly conserved amino acid and Y to C is a radical amino-acid change, compromising in vivo the interaction between BRCA2 and replication protein A (Wong et al, 2003). All splice site mutations were studied at the RNA level Claes et al, 2003).…”
Section: Brca1 and Brca2 Mutationsmentioning
confidence: 99%
“…Olson et al (24) have concluded that Ser 33 is modified by ATR. The remaining sites (Ser 4 , Ser 8 , Ser 11 , Ser 12 , and Ser 13 ) are phosphorylated in response to genotoxic stress, although the responsible kinase(s) in vivo has not yet been identified. However, all can be modified by DNA-PK in vitro (22).…”
mentioning
confidence: 99%
“…(That is, the initial modification of Ser 33 by ATR stimulates subsequent phosphorylation of Cdk sites Ser 23 and Ser 29 ). These events then facilitate modification of Thr 21 and extreme N-terminal sites Ser 4 and Ser 8 , probably by DNA-PK. Our data also indicate that the phosphorylation of one RPA molecule can influence the phosphorylation of other RPA molecules in trans.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the considered mutations showed a LOF by mainly disrupting transient protein-protein interactions. For instance, a mutation in BRCA2, a breast cancer related gene, impairs the interaction with the replication protein A complex, essential for DNA repair [24], which leads to an accumulation of carcinogenic DNA damages. Another case of a LOF mutation occurs in the von Hippel-Lindau (VHL) tumor suppressor gene involved in the VHL syndrome, an inherited predisposition to a variety of cancer types [25].…”
Section: The Role Of Connectivity In Human Diseasementioning
confidence: 99%